Good agricultural practices (GAP) in the Philippines status, issues, and policy strategies - Banzon, Agnes T.; Mojica, Loida E.; Cielo, Angela A. (Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA), 2013)
This study was undertaken to assess the status of good agricultural practices (GAP) adoption in the Philippines in relation to two of the country's top export fruit crops : Cavendish banana and Carabao or Super Manila mango. Specifically, the study aimed to identify the drivers of and constraints to GAP adoption for the two identified commodities in the study. Davao was selected as the study area for banana, being the country's top banana exporter. For mango, Zambales was chosen because it is the origin of the sweetest mango in the world.